STAT1 Isoforms Differentially Regulate NK Cell Maturation and Anti-tumor Activity - Meissl, Katrin; Simonović, Natalija; Amenitsch, Lena; Witalisz-Siepracka, Agnieszka; Klein, Klara; Lassnig, Caroline; Puga, Ana; Vogl, Claus; Poelzl, Andrea; Bosmann, Markus; Dohnal, Alexander; Sexl, Veronika; et al. (Frontiers in Immunology, 2020)
Natural killer (NK) cells are important components of the innate immune defense against infections and cancers. Signal transducer and activator of transcription 1 (STAT1) is a transcription factor that is essential for NK cell maturation and NK cell-dependent tumor surveillance. Two alternatively spliced isoforms of STAT1 exist: a full-length STAT1α and a C-terminally truncated STAT1β isoform. Aberrant splicing is frequently observed in cancer cells and several anti-cancer drugs interfere with the cellular splicing machinery. To investigate whether NK cell-mediated tumor surveillance is affected by a switch in STAT1 splicing, we made use of knock-in mice expressing either only the STAT1α (Stat1α/α) or the STAT1β (Stat1β/β) isoform. NK cells from Stat1α/α mice matured normally and controlled transplanted tumor cells as efficiently as NK cells from wild-type mice. In contrast, NK cells from Stat1β/β mice showed impaired maturation and effector functions, albeit less severe than NK cells from mice that completely lack STAT1 (Stat1-/-). Mechanistically, we show that NK cell maturation requires the presence of STAT1α in the niche rather than in NK cells themselves and that NK cell maturation depends on IFNγ signaling under homeostatic conditions. The impaired NK cell maturation in Stat1β/β mice was paralleled by decreased IL-15Rα surface levels on dendritic cells, macrophages and monocytes. Treatment of Stat1β/β mice with exogenous IL-15/IL-15Rα complexes rescued NK cell maturation but not their effector functions. Collectively, our findings provide evidence that STAT1 isoforms are not functionally redundant in regulating NK cell activity and that the absence of STAT1α severely impairs, but does not abolish, NK cell-dependent tumor surveillance.